Efektivitas LKS Pendekatan Saintifik Laju Reaksi dalam Meningkatkan KPS Berdasarkan Kemampuan Kognitif - Indra Muntari; Nina Kadaritna; Emmawaty Sofya (Jurnal Pendidikan dan Pembelajaran Kimia, 2017)
This study was aimed to describe effectiveness of student worksheets based-on scientific approach on factors affecting reaction rate and collision theory to increase science process skills based-on cognitive ability. Samples in this study are students of class XI IPA 4 and students of class XI IPA 1. The research method used is Quasi Experimental with The Matching Only Pretest and Postest Control Group Design. Instruments used were student worksheets based-on scientific approach and conventional, pretest and postest questions. Data analysis techniques used were two path anova test and t-test. The results of this study indicate that student worsksheets based on scientific approach are effective to increase science process skills of high cognitive ability students and low cognitive ability students; the application of student worksheets based-on scientific approach is not affected by students cognitive ability, increased of science process skill high cognitive ability students is not different as significant with low cognitive ability students.Penelitian ini bertujuan untuk mendeskripsikan efektivitas LKS berbasis pendekatan saintifik pada materi faktor-faktor yang mempengaruhi laju reaksi dan teori tumbukan dalam meningkatkan keterampilan proses sains (KPS) ditinjau dari kemampuan kognitif. Sampel dalam penelitian ini adalah siswa kelas XI IPA 4 dan siswa kelas XI IPA 1. Metode penelitian yang digunakan yaitu Quasi Experimental dengan The Matching Only Pretest and Postest Control Group Design. Instrumen yang digunakan adalah LKS berbasis pendekatan saintifik dan konvensional, soal pretes dan postes. Teknik analisis data yang digunakan yaitu uji anova dua jalur dan uji-t. Hasil penelitian menunjukkan bahwa LKS berbasis pendekatan saintifik efektif dalam meningkatkan KPS siswa kemampuan kognitif tinggi dan kognitif rendah; pembelajaran menggunakan LKS berbasis pendekatan saintifik tidak terpengaruh oleh kemampuan kognitif siswa; peningkatan KPS siswa kemampuan kognitif tinggi tidak berbeda secara signifikan dengan siswa kemampuan kognitif rendah.Kata kunci: kemampuan kognitif, KPS, LKS berbasis pendekatan saintifik